Kendala dalam Rantai Nilai Agribisnis Selada Baby Romaine (Lactuca Sativa Var.Romana L.) yang Berorientasi ke Pasar Retail Modern (Studi Kasus di PT. XYZ) - Simangunsong, Rezkia Theresia; Syamsiyah, Nur (Universitas Galuh, 2024)
Lettuce is one of the horticultural products that has high economic value and potential to be developed. This vegetable is in great demand by hotels, restaurants, and for export abroad. The high demand for lettuce is not matched by a high supply, so Indonesia must continue to import lettuce. In fact, according to the General Manager of PT XYZ, this product provides considerable profits for the company. At PT XYZ, one of the most popular products is baby romaine lettuce. This vegetable is grown organically using NFT hydroponic technology. This product is offered to modern retailers, hotels, restaurants, cafes, and end users with a price range of Rp15,000-Rp60,000 depending on the packaging. The purpose of this study was to determine the value chain of baby romaine lettuce commodities at PT XYZ for modern retail. The research design used is a qualitative approach with a literature study research method. The analysis used is descriptive analysis. The results showed that the company carried out value activities, especially the main activities and supporting activities. The constraints faced in the baby romaine lettuce value chain are unstable production, demand that tends to fluctuate, and product returns by consumers because the quality and quantity of products do not match consumer demand. The most crucial constraint is the unstable production because it makes it impossible for the company to fulfill consumer demand. In addition, the company still cannot find a solution to this problem.